Development of a food frequency questionnaire for assessing dietary intake in children and adolescents in South America (2018)
ABSTRACT: This study aimed to describe the development of a food frequency questionnaire (FFQ) to assess dietary intake in South American children and adolescents. Methods: A total of 345 children (aged 3-10 years) and 357 adolescents (aged 11-17 years) were included for analysis. The FFQ was designed to be self-administered and to assess dietary intake over the past 3 months. It was developed in Spanish and translated into Portuguese. Multiple approaches were considered to compile the food list, and 11 food groups were included. A food photo booklet was produced as supporting material. Results: The FFQ items maintained a common core list among centers (47 items) and country-specific foods. The FFQ for Buenos Aires and Lima had a total of 63 items; there were 55 items for the FFQ in Medelin, 60 items for Montevideo, 58 items for Santiago, 67 items for Sao Paulo, and 68 items for Teresina. Alcohol was also incorporated in the adolescents’ FFQ. Conclusions: We developed a semiquantitative, culturally adapted FFQ to assess dietary intake in children and adolescents in South America. It has an optimal size allowing its completion in a high proportion of the population; therefore, it can be used in epidemiological studies with South American children and adolescents.